Measuring the extent adopt of commercial banks operating in Algeria the pillars of total quality management from the employees' Point of View; a field of study « CPA, BNA, BBA » - Abdellatif Oulad Haimouda; Ahmed Almaoui; Mustapha Touiti (Dirassat Journal Economic Issue, 2020)
This study aimed to measure the extent adopt of commercial banks operating in Algeria the pillars of total quality management from the employees’point of view, and to address the main problem and prove the validity or not of the study hypotheses we conducted a field study approach at the banks of "CPA, BNA, BBA", where a survey was designed to include Phrases that measure the extent adopt of banks case study the pillars of total quality management, represented by, "based customer, staff training and qualification, focus on improving banking operations, the ability to measure the service performance quality in delivery", and the survey was delivered to a randomly sample of 189 employees, The most important results were: « The case study banks are take care of customer complaints and seek to provide the immediate solutions to them, the goal of the training programs carried out by the banks is to improve their banking products quality, the banks do not measure the Performance quality in all departments, the management of the banks depends on program that continuously reduces accounting errors, which is contributes to the management efficiency achievement ».